Young Workers on Digital Labor Platforms: Uncovering the Double Autonomy Paradox - Sloth Laursen, Cæcilie; Nielsen, Mette Lykke; Dyreborg, Johnny (Nordic Journal of Working Life Studies, 2021)
Drawing on interviews with 12 young adults in the Danish digital labor market, this article investigates how young workers on digital labor platforms experience the tension between ‘algorithmic management’ and autonomy. Digital labor platforms promise autonomy to workers, but the study shows that the platforms in varying degrees exert control over the labor process in different stages of the work. The inherent non-transparency of the algorithmic management systems makes it difficult for the young workers to understand the underlying mechanisms of the platforms. While the young workers’ autonomy in some important ways is restricted by the algorithmic management systems, the young workers have all chosen the platform work because they feel that it allows them to control where and when they work. We propose the conceptualization ‘the double autonomy paradox of young workers’ to describe this phenomenon.